Decoding Fenugreek’s Cholesterol-Lowering Mechanism: A Critical Review of its Therapeutic Potential - , Nadendla. Rama Rao, Akula. Venkata Bhuvaneswar, Anagani. Bhavya Sri, Pragada. Santhosh Kumar, Karedla. Sravani, Gollapothu. Krupanidhi, Maddineni Chiranjeevi, Ravuri. John Baniyan, Nagam. Venkata Pavan Aditya (Archives of Current Research International, 2025)
Background: Dyslipidemia is a major modifiable risk factor for cardiovascular diseases, the leading cause of mortality worldwide. The consolidation of interest in plant-based interventions has Spurred further examination of traditional medicinal herbs for their effect on lipid levels. Fenugreek (Trigonella foenum-graecum), an herb found in the traditional Ayurvedic and Chinese matrix, has emerged as a promising functional food. This is based on its phytochemical profile, in addition to its cardioprotective and health-promoting functions. Objective: This review sought to evaluate the lipid-lowering effects of fenugreek, describe potential biochemical and pharmacological mechanisms, and evaluate the clinical relevance of fenugreek is dyslipidemia and other metabolic states Methods: A comprehensive literature search was conducted using PubMed, Scopus, and Google Scholar, to identify relevant preclinical studies, clinical trials, and imaging and mechanistic studies published in the past 20 years. The key inclusion model was studies examining the effects of fenugreek seed, extract, or derived compounds on lipid profiles and cardiovascular characteristics in human and non-human subjects. Results: The chemical analysis revealed that fenugreek seeds are high in soluble dietary fiber (galactomannan), and abundant bioactive constituents, such as, steroidal saponins (e.g., diosgenin), flavonoids, polyphenols, alkaloids (e.g., trigonelline), and amino acids. Such constituents exert numerous lipid-modulating properties, such as: inhibit cholesterol absorption in the intestine; increase bile acid secretion; increase lipolytic enzymes; and downregulate the hepatic HMG-CoA reductase, which is the rate-limiting enzyme in cholesterol biosynthesis. Animal studies show that supplementation with fenugreek has significantly lowered total cholesterol, low density lipoprotein- cholesterol (LDL-C) and triglycerides, while simultaneously raising high density lipoprotein-cholesterol (HDL-C). The relatively few human clinical trials have also shown some encouraging data but sample sizes are too small and the studies too short in duration for any statistically valid claims. However, some literature exists documenting favourable changes in lipid profiles associated with fenugreek in patients diagnosed with hyperlipidemia, type 2 diabetes and metabolic syndrome. Fenugreek was also found to be highly palatable and offer multiple forms of consumption i.e. whole seeds, defatted powder (flour), aqueous extracts and nutraceutical formulations; thus, supporting potential for promotion, uptake and long-term consumption as dietary therapy. Conclusion: Fenugreek shows significant potential as an affordable, natural tool for the prevention and treatment of dyslipidemia and cardiovascular disease risk. Its diverse lipid-lowering mechanisms, benign safety profile, and straightforward incorporation into the diet classify it as a candidate for both pharmacological and dietary components of cardiovascular care. However, the present evidence base is limited by methodologic challenges, differences in primary extract type, and a lack of large and well-designed randomized controlled trials. Future research should focus on developing standard doses of fenugreek combined with safety and effectiveness studies designed and executed in large clinical trials to enable evidence-based recommendations for its inclusion in evidence-based treatment protocols.